2022
DOI: 10.5507/bp.2020.045
|View full text |Cite
|
Sign up to set email alerts
|

Combined and intravenous administration of TXA reduces blood loss more than topical administration in primary total knee arthroplasty: A randomized clinical trial

Abstract: Aim. To determine the most effective administration of tranexamic acid (TXA) in patients with primary total knee arthroplasty (TKA). Material and Method. We enrolled a total of 400 patients (154 men and 346 women) in this randomized trial (4 groups, each of 100 patients). The first group (IV1) had a single intravenous dose (15 mg TXA/kg) prior to skin incision. Group 2 (IV2) had TXA in 2 intravenous doses (15 mg TXA/kg): prior to skin incision and 6 hours after the first dose. Group 3 (TOP) had 2 g TXA in 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…TXA is a lysine derivative 10 that can be inhaled, applied topically, or given by intravenous (IV) administration 3,11 in order to systemically manage patient hemorrhage. Depending on the specific case, dosing recommendations have ranged from administering TXA at a dose of 15 mg/kg of body weight 12 to administering a bolus ranging from 1 to 4 g of TXA 13,14 . Some studies have experimented with providing multiple doses of TXA but have generally found similar outcomes between single and multiple-dose groups 15 .…”
mentioning
confidence: 99%
“…TXA is a lysine derivative 10 that can be inhaled, applied topically, or given by intravenous (IV) administration 3,11 in order to systemically manage patient hemorrhage. Depending on the specific case, dosing recommendations have ranged from administering TXA at a dose of 15 mg/kg of body weight 12 to administering a bolus ranging from 1 to 4 g of TXA 13,14 . Some studies have experimented with providing multiple doses of TXA but have generally found similar outcomes between single and multiple-dose groups 15 .…”
mentioning
confidence: 99%